POLITICAL LAW IN SETTLING SPORTS DISPUTES IN INDONESIA - Christiana Sri Murni; Fradhana Putra Disantara; Dicky Eko Prasetio (Kanun Jurnal Ilmu Hukum, 2023)
This research aims to examines political law in sports disputes and efforts to regulate the future of political law in settling disputes  in the Act Number  11,2022 concerning Sports within progressive legal perspective. The research shows that the problems of legal politics in sports disputes is that the principles of lex sportiva and  lex ludica have not been implemented in the settlement of sports disputes by involving the main sports’ branches organization. In addition, the politics of law in sports disputes are also related to the potential for dualism in the sports arbitral bodies that are  National Sport Committee (KONI) and National Olympic Committee (KOI). The efforts to regulate sports dispute  require a legal reform in the form of a revision of the provisions of the Sports Law in emphasizing three important aspects, namely providing definitions and boundaries regarding sports disputes, affirming the main role of sports branch organizations as an implementation of the lex sportiva and the principle of lex ludica, as well as affirmation to guarantee legal certainty regarding the potential dualism of sports arbitral bodies.